Cloud Computing Delivery and Delivery Models: Opportunity and Challenges - Alajmi, Qasim; Sadiq, Ali Safa; Adzhar, Kamaludin; Al-Sharafi, Mohammed A. (American Scientific Publisher, 2018)
The rapid growth of Internet and computing field results in several technological advantages. In the meanwhile, security challenges that emerge along with the growth complicate the aspects of cloud based computing. Security is by now one of the most pressing concerns in Internet business where cloud computing lies in. Cloud-based services are evolving each day introducing new business trends. Since cloud computing entails storage of information in remote servers, unauthorized access to such sensitive information becomes a looming concern. The advantages offered by cloud computing, without robust security measures and flexibility, could lead to lose its credibility. This paper reviews various aspects of cloud computing and issues inherent within its contexts. This paper has identified the gap within the topic of study through the creation of the conceptual framework, which is designed as the way of attempting to connect the different concepts. The intention of the theoretical framework is to determine the potential gaps in the research and link the gaps by the present study and its results. The delivery of both, the cloud computing as well as its models is a relatively new phenomenon within the academic libraries where the study is at the stages of nascent. The conceptual framework could not be comprehensive. Instead, it was a progressive work. Thus, this new topic could be added to form the branch within the theoretical framework. This article tries to look at different concepts of cloud computing as well as the issues, which are inherent within its contexts. It analyzes this part due to the advent and growth in the sector of cloud computing, which is developing the platform for the computing in the future.